On the development of volitional activity in mentally deficient pupils - Laužikas, J. (Psichologija, 1968)
Soviet psychology pays much attention to issues associated with the development of the human psyche. The research works by A. Leontyev, L. Bozhovich, D. Elkonin, A. Liublinskaya and other soviet psychologists disclose important issues of the psychic development of children. It is maintained in their works that psychic progress is better determined by the influence of diverse activities rather than by innate natural qualities. L. Zankov, G. Kostyuk, N. Menchinskaya and other psychologists demonstrated the interaction between the learning and development. Soviet psychology regards the purposeful activity and work of a person as the key factor for human development. Numerous research works on psychic development bring mental activities to the forefront, whereas volitional activity is either subjugated to the mental processes or remains ignored. However, any conscious processes are associated with willful attempts and their regulation. Volitional activity has not been properly investigated yet. To explain the development of mentally deficient children, cognitive processes have been mostly examined. On the other hand, passiveness and deficiency of relations with the outer world weaken activities and psychic development of mentally retarded children. Without active engagement, mental abilities and self-will are devoid of proper development. We have decided to explore the development of volitional activity and efficiency qualities of junior students. To this end, students’ day-to-day activities and learning have been monitored, psychological experiments have been performed and certain regulatory methods of upbringing, activity and behavior have been applied. For purposes of cultivation of willpower in students, the following principles have been applied: l) activity and work, 2) courage and confidence, 3) expedience and perspective, 4) individual approach and individualization, 5) appropriateness and consistency, 6) uniform requirements and impact. These principles have been observed by both teachers and mentors. According to the type of high nervous activity, two groups of children have been distinguished: active or excitable, and passive or suppressive children. The attempts to regulate the activeness of the excitable children have been made by training their self-control and self-command skills, while the suppressive children have been boosted and encouraged. The examined students have been closely watched in various circumstances. The data of monitoring and a-year-after control experiments have clearly established that the willful activity in the examined students has developed more than in students of the control group. It has been also established that activated qualities of self-will have been developing faster than self-control and regulatory qualities. Apparently, self-command and endurance require more willpower than activeness. The development of self-will in students has also affected their mental processes and learning efficiency, behavior and interrelations.